A study on an early Neolithic site in North China - Zhao, Chaohong (Documenta Praehistorica, 2003)
These are few sites about 10 000 BP in the early Neolithic period in North China; among these, the Donghulin site is the only one which included the remains of peoples' use of fire (hearth pits), stone implements, pottery objects, and human tombs. The excavation of the Donghulin site in 2001 provides very important information for research on people and culture in the early Neolithic period in North China. The finding of Donghulin Man has filled the gap in our knowledge of human development since the period of the "Upper Cave Man" (30 000a BP) in North China. It is also important for research on people-land relationships.
Keywords: archaeology; arheologija; neolitik; Kitajska; ceramic; keramika; najdišča